Impact of waiting time on customer satisfaction and loyalty at fast food restaurant in Malaysia / Nur Salsadilla Zainudin & Nur Fatin Amaniena Zulkiflee - Zainudin, Nur Salsadilla; Zulkiflee, Nur Fatin Amaniena (Faculty of Hotel and Tourism, 2018)
Waiting time relates closely especially when it comes to service. Waiting time requires the customer to wait in order before they can feel or receive the actual action. It will determine their satisfaction level. This research is about to study the impact of waiting time on customer satisfaction and loyalty at the fast food restaurant. Waiting time can influence customer whether gives positive or negative impacts towards the restaurant. Customer satisfaction in the aspect of businesses is important when providing service because they are the main contributor to the business success and can be as attracting factor that will make customer to continuously patronize the service. Furthermore, it also reflects the service quality provided to the customer by measuring their satisfaction level. Satisfaction level can be obtained only when customers’ expectations are met and they enjoyed with the service given. Thus, a loyalty bond or relationship can be formed when they are feeling satisfied with the waiting time and the quality of service served to them which will make them revisit or repeat their purchasing at the place in future.